Effect of harvesting time in growth performance and energy crops productivity of Napier (Pennisetum purpureum cv. Taiwan) exposed under CO2 elevated conditions - Mohd Nasirudin, Muhammad Zulhilmi; Sakimin, Siti Zaharah; Yahya, Liyana; Zainal, Afifi; Omar, Noraziah Muda; Jusoh, Shokri; Sinniah, Uma Rani (Universiti Putra Malaysia Press, 2024)
Napier grass is crucial in reducing greenhouse gas emissions by substituting non-renewable resources. When Napier grass is burned, the carbon dioxide (CO2) released is roughly equal to the amount absorbed during its growth, making it a potentially carbon-neutral energy source. This study investigates the impact of ratooning (repeated harvesting) on various aspects of Napier grass, including growth, physiology, biomass production, nutrient content, and chemical analysis. It also explored the interaction between elevated CO2 levels and ratooning. Two experiments were conducted over 12 months. Experiment 1 took place in an open field at the Faculty of Agriculture, Universiti Putra Malaysia (UPM), with two treatments: no ratooning and ratooning at three months after planting (MAP). Experiment 2 was conducted in an open field at UPM and a greenhouse at Tenaga National Berhad Research, Kajang, Selangor. Eight combination treatments were studied: (T1) 1-month elevated CO2 (MECO2) - no ratooned, (T2) 1 MECO2-R at 3 MAP, (T3) 2 MECO2-noR, (T4) 2 MECO2-R at 3 MAP, (T5) 5 MECO2noR, (T6) 5 MECO2-R at 3 MAP, (T7) 12 MECO2-noR, and (T8) 12 MECO2-R at 3 MAP. The results indicated that, in Experiment 1, no ratooning was more favourable for all parameters compared to ratooning. In Experiment 2, a 1-month exposure to elevated CO2 showed better results compared to longer exposure periods. In conclusion, Napier grass performed better when not subjected to ratooning and exposed to short-term elevated CO2 levels. This research highlights the potential of Napier grass as a sustainable and carbon-neutral energy source.